2000
DOI: 10.1038/sj.bjp.0703222
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of the HERG human cardiac K+ channel by the antidepressant drug amitriptyline

Abstract: 1 Amitriptyline has been known to induce QT prolongation and torsades de pointes which causes sudden death. We studied the e ects of amitriptyline on the human ether-a-go-go-related gene (HERG) channel expressed in Xenopus oocytes and on the rapidly activating delayed recti®er K + current (I Kr ) in rat atrial myocytes. 2 The amplitudes of steady-state currents and tail currents of HERG were decreased by amitriptyline dose-dependently. The decrease became more pronounced at more positive potential, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 33 publications
4
41
1
Order By: Relevance
“…The mechanism of this effect was not explored but theoretically could involve a reduction in haloperidol binding (either by direct competition or via an allosteric effect), interference with the transduction mechanism by which haloperidol binding results in closure of the channel, or, if the drug interacts preferentially with a particular gating state, an effect of external potassium ions on gating. It has been shown that the binding of open channel blockers, including haloperidol, to voltage-gated potassium channels are reduced at higher [K þ ] o (Kuo, 1998;Jo et al, 6770.25, 3.0670.65, 8.9770.95, 14.8472.75, and 23.8872 Shuba et al, 2001). The detailed mechanism is still not clear, but it has been proposed that external potassium ions compete with the open channel blocker imipramine for binding to the external pore region of the A-type potassium channel in rat hippocampal neurons (Kuo, 1998 Kobayashi et al, 2000), which may possibly lead to underestimation of the safety margin of these compounds as is the case for haloperidol (Redfern et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of this effect was not explored but theoretically could involve a reduction in haloperidol binding (either by direct competition or via an allosteric effect), interference with the transduction mechanism by which haloperidol binding results in closure of the channel, or, if the drug interacts preferentially with a particular gating state, an effect of external potassium ions on gating. It has been shown that the binding of open channel blockers, including haloperidol, to voltage-gated potassium channels are reduced at higher [K þ ] o (Kuo, 1998;Jo et al, 6770.25, 3.0670.65, 8.9770.95, 14.8472.75, and 23.8872 Shuba et al, 2001). The detailed mechanism is still not clear, but it has been proposed that external potassium ions compete with the open channel blocker imipramine for binding to the external pore region of the A-type potassium channel in rat hippocampal neurons (Kuo, 1998 Kobayashi et al, 2000), which may possibly lead to underestimation of the safety margin of these compounds as is the case for haloperidol (Redfern et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Electrocardiogram abnormalities are frequent, and a wide variety of cardiac arrhythmias can occur, the most common being sinus tachycardia and intraventricular conduction delay (QRS prolongation) (36). Previous studies have shown that tricyclic antidepressants modulate sarolemmal ion channels involved in cardiac excitation-contraction coupling (6,13,19). The aim of the present study was to investigate effects of AMT on SR Ca handling in ventricular myocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In cellular electrophysiological studies, it has been shown that citalopram has a high degree of potential to inhibit the K + current which is responsible for the action potential repolarization phase in the heart; the prolongation of the QTc interval induced by a toxic dose of citalopram is associated with this condition. Also, it has been shown that citalopram causes a prolongation in action potential time, a prolongation of the QTc interval, as well as an increase in torsade de pointes risk and sudden death by inhibiting G-protein activated inward rectifier potassium channels (GIRK) and hERG potassium channels (17)(18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%